2021
DOI: 10.1080/19768354.2021.1943708
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone-like and follicle-stimulating hormone-like activities of equine chorionic gonadotropin β-subunit mutants in cells expressing rat luteinizing hormone/chorionic gonadotropin receptor and rat follicle-stimulating hormone receptor

Abstract: 2021): Luteinizing hormone-like and follicle-stimulating hormone-like activities of equine chorionic gonadotropin β-subunit mutants in cells expressing rat luteinizing hormone/chorionic gonadotropin receptor and rat follicle-stimulating hormone receptor, Animal Cells and Systems,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…For rec-eCGβ/α production, the expression vectors were transfected into CHO-S cells using the FreeStyle™ MAX reagent, following the manufacturer’s instructions [ 41 , 42 ]. Briefly, the CHO-S cells were cultured in FreeStyle CHO expression medium at 1 × 10 7 cells per 30 mL of medium for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…For rec-eCGβ/α production, the expression vectors were transfected into CHO-S cells using the FreeStyle™ MAX reagent, following the manufacturer’s instructions [ 41 , 42 ]. Briefly, the CHO-S cells were cultured in FreeStyle CHO expression medium at 1 × 10 7 cells per 30 mL of medium for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…The second messenger kinases of β ARK and GRK phosphorylate serine and/or threonine residues in the intracellular region of GPCRs following agonist-induced treatment ( Kim et al, 2018 ). We and others have shown that ligands (hCG, eCG, eFSH, eel FSH, and eel LH) of glycoprotein hormone receptors result in the accumulation of cAMP responses ( Hipkin et al, 1995a , b ; Min et al., 2004 ; Bhaskaran & Ascoli, 2005 ; Kim et al, 2018 ; Byambaragchaa et al, 2021c , d , 2022 ). Several features of the post-endocytotic trafficking of receptors (mouse, rat, and human) that demonstrate routing of most internalized receptors to the lysosomes, and degradation of hormone-receptor complexes have been elucidated ( Baratti-Elbaz et al, 1999 ; Kishi et al, 2001 ; Bhaskaran & Ascoli, 2005 ).…”
Section: Discussionmentioning
confidence: 97%
“…The supernatant was collected and concentrated using a Centricon filter. Finally, the sample was mixed 10–20 times and the quantity of rec-eCG was determined using ELISA as previously reported ( Byambaragchaa et al, 2021c , d ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the intracellular signal transduction to cAMP via LH receptors, the amino acid residues 102 -104 of the β-subunit of sc eCG were replaced. The Rmax value of mutant eCG at amino acid 104 was the lowest, which means that this amino acid plays an essential role in the intracellular signal transduction to cAMP through LH receptors (Byambaragchaa et al, 2021b).…”
Section: Recombinant Equine Chorionic Gonadotropin (Rec-ecg)mentioning
confidence: 95%